Morally blameless wrongdoers and the change of position defence - Rotherham, Craig (Singapore Academy of Law, 2018)
This article argues that, contrary to the position taken by some judges and commentators, morally blameless defendants who have committed torts of strict liability should be able to raise the change of position defence against claimants who sue for a release fee (also known as “Wrotham Park damages”). For the defence to be available, however, release fees need to be understood not as compensatory, as many currently insist, but as gain-based. The defence should not necessarily be available in the context of restitution for wrongs to all defendants who have changed position in good faith, as is the case for unjust enrichment by subtraction. Those who changed position by dissipating wealth for their own benefit should be denied the defence if their breach of the claimant’s rights was careless. Defendants who, in contrast, altered their circumstances in such a way that they derived no net enrichment as a result of their wrong should be allowed to rely on the defence, even if they acted without care.